Rehearsal in spatial working memory: evidence from neuroimaging. - Awh, Edward; Jonides, John; Smith, Edward E. (Psychological Science., 1999)
The writers tested the hypothesis that the active rehearsal of spatial information in working memory is accomplished by means of focal shifts of spatial selective attention to memorized locations. They employed functional magnetic resonance imaging to observe posterior visual activations during the performance of a spatial working memory task. They contend that in line with the hypothesis, spatial rehearsal led to improved activation in the early visual areas contralateral to the memorized locations.